Synergetic effects of Kevlar fibers and polyimide powder fillers on performances of Poly(diaryloxyphosphazene) based elastomeric heat shielding materials. (26th May 2022) - Wu, Jian; Zhang, Shuangkun; Wang, Lianqing; Lin, Husitu; Liu, Wei; Wu, Dezhen; Wu, Zhanpeng
Abstract: Poly(diaryloxyphosphazene) (PDPP) represent the state-of-the-art alternative and promising elastomeric heat shielding materials (EHSMs) for solid rocket motors due to its better ablative performance and unique charred layers. Kevlar fibers (KF) usually constitutes the common fibrous reinforcement for PDPP based formulations of EHSMs because KF is a kind of organic fiber with heat resisting available at a lower price, and there is strong interfacial bonding between fibers and PDPP matrix. To increase the mechanical and ablation properties of PDPP based KF composites, polyimide powders (PIP) is considered here in the material formulation because of good dispersion effects of PIP into matrix and its excellent thermal stability. In this work, dense and intact charred layers were constructed via the combination of KF and PIP into the PDPP based formulations of EHSMs. The results have showed that the tensile strength and ablation properties exhibited a significant increase with addition of PIP. At combination of 9 phr KF and 10 phr PIP in formulations, the mass ablation rate reduced to 0.044 g/s, which was 40.5% lower than that of insulation filled with only KF fillers. Furthermore, micro-computed tomography (micro-CT) was used for the first time to characterize morphology of charred layers of the ablative composites. It was indicated that no ply delamination and interfacial debonding were found between charred layers and beneath virgin materials. This study provides an effective approach to prepare a new EHSMs system, which can be applied in new potential aerospace vehicles. Graphical abstract: Image 1